2024
DOI: 10.2166/aqua.2024.243
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of water hyacinth (Eichhornia crassipes) biomass as eco-friendly sorbent for petroleum oil spill cleanup

Marufa Khondoker,
Ranjit Gurav,
Sangchul Hwang

Abstract: This study focuses on the removal of spent engine oil (SEO) spill from the water surface using water hyacinth biomass (WHB)-based sorbents. The raw WHB was modified using extra virgin coconut oil (mainly consisting of lauric acid) to enhance the hydrophobicity and floating ability. With varying amounts of coconut oil and solvent, six diverse types of modified water hyacinth biomass (MWHB) were prepared. Among these MWHBs, an equal proportion of coconut oil and raw WHB with 10% methanol solution exhibited the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated the efficacy of water hyacinth biomass as a viable sorbent for the removal of PDPs. The biomass was mixed with varying quantities of coconut oil to increase its hydrophobicity and was then capable of removing above 90% of a simulated oil spill, even after a third sorption–desorption cycle [ 106 ].…”
Section: Removing/containing Actionsmentioning
confidence: 99%
“…A recent study demonstrated the efficacy of water hyacinth biomass as a viable sorbent for the removal of PDPs. The biomass was mixed with varying quantities of coconut oil to increase its hydrophobicity and was then capable of removing above 90% of a simulated oil spill, even after a third sorption–desorption cycle [ 106 ].…”
Section: Removing/containing Actionsmentioning
confidence: 99%